A study to assess the effectiveness of a structured teaching programme on knowledge, attitudes and impacts regarding energy shot among adolescents at P. P. Savani Chaitanya Vidya Sankul, Surat - Alias Rathinam, Vadivazhagan; Chaudhary, Parimal; Rawal, Milan; Abdullahi, Muhammad Mahmud; Modu, Wakil; Patel, Ekangi; Patel, Dhruvi; Parmar, Mona; Verma, Hemanti (International Journal Of Community Medicine And Public Health, 2025)
Background: Energy shots can be described as beverages that contain large quantity of caffeine and other legal stimulants used to boost a person’s physical and cognitive activities beyond the normal range. The main aim of this study was to estimate the effectiveness of structured teaching programme given to adolescents of P. P. Savani Chaitanya Vidya Sankul, in regards to their knowledge and attitudes towards energy shot, and its impacts to them. Methods: In this study, a quasi-experimental research design was adopted with 60 samples used. A self-structured questionnaire was used to collect the data. The collected data were analysed and interpreted using descriptive and Inferential statistics. Results: The present study has justified the effectiveness of the structured teaching programme, where it showed the post-test knowledge mean score 16.8167 higher than the pre-test knowledge mean score 9.5833 with mean difference score of 7.2333. Again, the post-test attitude mean score 33.4833 was higher than the pre-test attitude mean score 32.9500, with a mean difference score 0.5333. Conclusions: The study was concluded with accepting the alternative hypothesis that emphasised the presence of significant difference between pre-test and post-test assessment. Hence, proving the structured teaching programme to be effective in increasing knowledge and positively modifying attitude among the samples.